1998
DOI: 10.1021/jp973381k
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Studies of the Interaction of Methanol with Cun, Agn, and Aun

Abstract: Methanol (Me) adsorbs intact on copper, silver, and gold clusters at 70 K to form the complexes Cu n Me m , Ag n Me m , and Au n Me m , respectively. The infrared photodissociation spectra of the deuterium-substituted complexes M n (CD 3 OH) m and M n (CD 3 OD) m (M n ) Cu 3-11 , Ag 3-22 , and Au 3-13 ) have been recorded in the 9-11 µm region. The methanol C-O stretching band frequency is invariant with cluster size and depends only slightly on the metal of which the underlying cluster is composed, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 71 publications
5
58
0
Order By: Relevance
“…Yet, the repulsive contributions of the CH 2 and CH 3 sites are felt at greater distances from the Au atoms than the one of the H site, due to their bigger size. These behaviours are in accordance with the insights provided by ab initio, DFT and experimental studies [9][10][11][12]. …”
Section: Fitting the Potential Energy Surfacesupporting
confidence: 89%
“…Yet, the repulsive contributions of the CH 2 and CH 3 sites are felt at greater distances from the Au atoms than the one of the H site, due to their bigger size. These behaviours are in accordance with the insights provided by ab initio, DFT and experimental studies [9][10][11][12]. …”
Section: Fitting the Potential Energy Surfacesupporting
confidence: 89%
“…A few include investigations of cluster reactions (201-204) on gas-phase oxide clusters and extensive work on pure metal clusters (205)(206)(207)(208)(209). For example, it has been shown (210) that reactions of Mo x O y ϩ with methanol display close similarities with the reactions of methanol over heterogeneous and homogeneous catalysts containing molybdenum-oxygen sites (211).…”
Section: ϫmentioning
confidence: 99%
“…Studies of the interaction of methanol [13][14][15] and ethanol [16] with gold clusters showed that these molecules adsorb on the clusters through the O atom, similarly to water. All the calculations were performed using the Gaussian 98 software package [17].…”
Section: Dft Calculationsmentioning
confidence: 99%
“…Experimental and theoretical works on the adsorption of methanol, and more recently of ethanol, on gold clusters [13][14][15] showed that methanol and ethanol adsorb intact on gold clusters. Furthermore, the binding occurs through the O atom of the hydroxyl group and always with the less coordinated available Au atom of the cluster.…”
Section: Dft Calculationsmentioning
confidence: 99%